Development of a reinforced concrete design application by Python - Amphon Jarasjarungkiat; Phanusit Srijarattanon; Phumin Predatham; Puttanun Hankla (My University, 2021)
The design of reinforced concrete structures is the foundation of civil engineering. Nowadays, a large number of computer programs are used for structural analysis and design but those programs are expensive to get licenses including unknown sources of information. In this research, the purpose is to develop an application that can design reinforced concrete structures according to ACI 318-95 standard based on residential reinforced concrete structures. Furthermore, Python is used to develop all of the procedures. The developed application is capable to receive data from analytical programs, design and display the result as graphics. Moreover, it can be printed as an efficient construction drawing being convenient for the users. Finally, this research will be an alternative for users who are interested to use a free and accurate application to design reinforced concrete structures.
Keywords: Python; BIM and Construction Integration